Model Thompson Untuk Eksplorasi Pemanfaatan TI pada UKM Tenun Songket Palembang - Irma Salamah; Asriyadi Asriyadi; Tri Rizkiah (Ikatan Ahli Informatika Indonesia, 2018)
SME’s songket weaving is a small business that utilizes information technology as a business strategy such as marketing tools that penetrate national borders. The famous SME’s songket woven fabric is in Palembang, where songket woven fabric is a typical handicraft of Palembang city. This study is aimed at testing and analyzing the factors that influence information technology utilization in the songket woven SME’s. The method that supports the use of information technology is the Thompson method. The factors analyzed were Social Factors, Affect, Complexity, Job Fit, Long Term Consequences and Facilitating Conditions that utilize of information technology. The sample of this study is 90 employees of 25 SME’s songket woven cloth who have used information technology in their business processes. The results of this study are the Affect, Complexity, Job Fit, Long-Term Consequences variables that do not affect the use of information technology, while the Social Factor, and Facilitating Conditions influence the use of information technology..